1981
DOI: 10.1084/jem.154.6.1732
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for immunoglobulin Fc on pathogenic but not on nonpathogenic protozoa of the Trypanosomatidae.

Abstract: The mechanisms parasites have developed to escape immune surveillance are currently under investigation in many laboratories, because their elucidation may provide new approaches to the prevention of the diseases the parasites cause. For a detailed description and experimental evidence of these various mechanisms, see the recent review by Bloom (1).One possible means of evasion is the uptake of host antigen by the parasite (2). This phenomenon has been amply studied and documented in schistosomiasis. The acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 27 publications
1
19
0
2
Order By: Relevance
“…It is also highly likely that FcBCC is at least in part responsible for the rapid NK cell clearance of oncolytic HSV1 in the setting of malignant glioma (Alvarez-Breckenridge et al, 2012), and clearance of infection by many other members of the herpesviridae family encoding similar or identical Fc-binding proteins (Corrales-Aguilar et al, 2014; De Miranda-Santos and Campos-Neto, 1981; Litwin et al, 1992; Loukas et al, 2001; Olson et al, 1997; Sprague et al, 2008). Given the presence of IgG binding proteins in many different pathogens, FcBCC may have broad implications in controlling infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is also highly likely that FcBCC is at least in part responsible for the rapid NK cell clearance of oncolytic HSV1 in the setting of malignant glioma (Alvarez-Breckenridge et al, 2012), and clearance of infection by many other members of the herpesviridae family encoding similar or identical Fc-binding proteins (Corrales-Aguilar et al, 2014; De Miranda-Santos and Campos-Neto, 1981; Litwin et al, 1992; Loukas et al, 2001; Olson et al, 1997; Sprague et al, 2008). Given the presence of IgG binding proteins in many different pathogens, FcBCC may have broad implications in controlling infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The role of antibody production as a secondary mechanism of immune control can be explained by the requirement for these antibodies to mediate or potentiate the clearance of released amastigotes. Antibodies may also be important in the killing of trypomastigotes although a considerable body of literature documents the multiple mechanisms by which trypomastigotes of T. cruzi may evade such antibody‐mediated destruction (De Miranda‐Santos and Compos‐Neto, 1981, Krettli and Brener, 1982, Schenkman et al . 1986, Sher et al .…”
Section: Discussionmentioning
confidence: 99%
“…In realty, approximately 10 times more normal IgG was required to provide the same levels of fluorescence intensity given by the IgG anti-Lmsp1 antibody. Indeed, the binding of normal immunoglobulin to an immunoglobulin ligand on the cell surface (Fc-like receptor) of members of the family Trypanosomatidae was proposed many years ago (20) and has been confirmed (25,35). However, the results presented here with purified rabbit IgG anti-Lmsp1 antibody clearly showed that the fluorescence intensity observed with this purified antibody molecule was markedly higher than the fluorescence intensity given by immunoglobulins present in the normal rabbit serum.…”
Section: Vol 71 2003mentioning
confidence: 99%
“…It is believed that these parasite ligands offer both an effective mechanism for antigen mimicry of the host antigens and an effective system for the internalization of the parasites in their target host cells. One possible parasite noncognitive ligand of immunoglobulins is an Fc-like receptor present on the cell surface of several members of the Trypanosomatidae (20,25,35). Indeed, immunoglobulins and purified Fc fragments of immunoglobulin G (IgG) have been shown to facilitate the internalization of Trypanosoma cruzi in their host cells and to consequently increase the infective capacity of these parasites (1,22,23,35).…”
mentioning
confidence: 99%